Morphometry and subpopulation of llama (Lama glama) sperm using the ISAS® CASA-Morph system - Cucho, Hernán (2021)
The aim of this study was to determine the existence of sperm subpopulations according to the morphometry of llama sperm, using a CASA-Morph system. Semen was collected from four 4-6-year-old Q'ara llamas by electroejaculation four times per animal, at one week intervals. The volume, total motility, sperm concentration, percentage of live sperm and percentage of sperm with acrosomal reaction were determined. The morphometric parameters of the sperm were evaluated using the CASA-Morph, Integrated Semen Analysis System (ISAS®v1). The length, width, area, perimeter, ellipticity, elongation, regularity and rugosity of the llama sperm head were determined, as well as the width, area, and distance and angle of insertion of the midpiece of the spermatozoa. The morphometric variables were distributed in five main components (PCA) called elongation, length, circularity, width of the midpiece and insertion of the midpiece, which explained 81.6% of the total variance. The cluster analysis determined four subpopulations (SP): SP1 grouped small cells with low elongation and ellipticity (36.8%); SP2, spermatozoa of intermediate size, both in length and width of the head (9.9%); SP3 of elongated cells with low head and midpiece width values (33.0%); and SP4 of sperm with a high midpiece width (20.2%). Significant differences were found for intra- and inter-animal subpopulations.